Confidentiality in Digital Health Records: Aligning Privacy and Care Advancement in Hospitals - Ari Andayani; Siska; Sagung Putri Purwani (Journal of Law, Politic and Humanities, 2024)
The development of medical services is undergoing a period of transformation towards digitalization. One form of medical services development in Indonesia is electronic medical records. Electronic Medical Records can help facilitate health services, but on the one hand, Electronic Medical Records can potentially pose a risk of patient data leakage. The purpose of the study is to analyze the responsibility of hospitals in the management of Electronic Medical Records and analyze the legal protection of patients in maintaining the confidentiality of Electronic Medical Records data. This research is a type of normative legal research with a Case Approach and a Statue Approach. The method of data collection is through literature study, and data analysis techniques are used through qualitative descriptive analysis. The research results stated Hospital's accountability in the management of Electronic Medical Records is to apply the principles of data security, restrict access to Medical Records, and store data. Meanwhile, the legal protection of patients to maintain the confidentiality of Electronic Medical Record data is the use of electronic signatures as a verification tool and provides criminal sanctions for violators in the form of fines, imprisonment, and dissolution of corporations.